On the anticrowding population dynamics taking into account a discrete set of offspring - Repšys, Šarūnas; Skakauskas, Vladas (Lietuvos matematikos rinkinys, 2015)
A model of a population dynamics is solved numerically taking into account a discrete set of offsprings and the nonlinear (directed) diffusion. The model consists of a system of integro-partial differential equations subject to conditions of integral type. A spread of initially lokalized population is studied. Some numerical results are discussed.